Human breastfeeding as a bio-psycho-cultural practice - Rodríguez, Keilyn (2018)
This article offers an analysis of 101 reports of empirical research from the medical and social sciences on human breastfeeding. We find two axes of research; one on the relationship between breastfeeding and human health and the other on breastfeeding as a bio-psycho-cultural phenomenon. The research evidences the importance of this evolutionary and nutritional practice for the human being, its use as an affective mechanism and the universality of human breastfeeding. Although is a culturally deferred practice.